Produção de forragem e comportamento de ovinos em pastagens com capim-marandu sob estratégias de rebaixamento para o diferimento - Rocha, Gabriel de Oliveira (2022)
The objective with this work was to verify if different lowering strategies (LS) of the pasture before the stockpiling alter the population density and the growth of basal and aerial tillers; pasture production and structure during the stockpiling period; and the ingestive behavior, consumption and performance of sheep in winter in pastures with marandu grass (Urochloa brizantha Hochst ex A. Rich Stapf “marandu”). Pastures were maintained at three average heights (15, 25 and 35 cm) for five months, and then those with 25 and 35 cm were lowered to 15 cm at the beginning of the stockpiling period (SP), totaling three combinations of treatments: 35/15, 25/15, in lowered pastures, and 15 cm, kept at this height all the time before stockiling. Pastures with 15 and 25 before stockpiling had a higher amount of basal tillers, but a lower number of aerial tillers, when compared to pasture managed with 35 cm. The tiller population decreased from the beginning to the end of the SP. LS did not influence aerial tiller morphogenesis during SP. The basal tiller showed a higher rate of elongation and stem length in the 15 pasture, compared to the others. Morphogenic characteristics, with the exception of leaf lifespan, were also lower at the end of SP than at the beginning for basal and aerial tillers. The pasture managed with 35/15 showed higher forage mass and, in general, higher percentages of live and dead stems, but lower plant area index, number of total tillers and tillers with apical meristem at the beginning of the SP. In addition, pasture under 35/15 produced less forage, compared to those managed with 15 and 25/15. At the end of the SP, the forage mass and the percentages of live and dead leaves did not vary between the LS. The pasture under 15 showed the highest percentage of live stems and number of reproductive tillers at the end of the SP. Nutrient intake and digestibility by sheep were not influenced by LS. However, DM intake, expressed as a percentage of body weight, CP intake and NDF digestibility were lower in the middle than at the beginning and end of the grazing period. Animal performance was also not influenced by LS, but decreased throughout the grazing period. Therefore, pasture lowering from 35 to 15 cm before SP reduces forage production and the percentage of stem in stockpiled forage. Keeping the pasture under 15 cm before SP optimizes forage production, but increases indlorescence’s tiller and, in effect, the participation of the stem in the forage produced. However, LS do not change animal consumption and performance. All the stockpiling strategies evaluated in this work can be used, according to the rancher’s objective. Lowering the pasture from 35 to 15 cm before PD results in a more suitable pastoral environment for the animal during the winter.